Bahasa Inggris - Al Khudri Sembiring; Rahmat Ramadansur; Marta Dinata; Della Julia (Universitas Negeri Jakarta, 2026)
Biology learning becomes meaningful when students can explain how organs, enzymes, and nutrients interact as an integrated physiological system. Yet digestive physiology is often reduced to memorized labels, leaving a representational gap in how learners reason about invisible biochemical processes. Addressing this gap, this study examined the uniqueness of Canva-supported Project-Based Learning (PjBL) as a student-generated visual representation strategy for strengthening critical thinking and cognitive learning outcomes in the human digestive system. A quasi-experimental pretest-posttest control group design was implemented with 66 Grade XI students selected through purposive sampling at a public senior high school in Riau Province, Indonesia. Students were assigned to an experimental class taught through Canva-integrated PjBL and a control class taught through conventional instruction. Data were collected using critical thinking essays, cognitive tests, observation sheets, and student response questionnaires, then analyzed through baseline comparison, independent-samples testing, and normalized gain. Initial ability was comparable between groups (p = 0.385), but the experimental class achieved significantly higher posttest scores in cognitive learning outcomes (82.62 vs. 73.13) and critical thinking (82.52 vs. 73.08), with p < 0.001. N-gain results also favored the PjBL class for cognitive achievement (0.65 vs. 0.47) and critical thinking (0.61 vs. 0.41). High implementation fidelity (95.24%) and positive engagement supported these gains, although scheduling remained a self-regulation challenge (76.14%). The study contributes evidence that digital artifact-based PjBL can move biology instruction beyond recall toward mechanistic reasoning, with broader implications for designing student-centered, representation-rich biology education in complex physiology topics.